PENDIDIKAN KARAKTER MELELUI EKSTRAKURIKULER KUNTAU DI SMAN 1 TANJUNG KECAMATAN MURUNG PUDAK KABUPATEN TABALONG - Endang Lestari (Universitas Lambung Mangkurat, 2015)
This study aims to determine whether the student's character can be formed through extracurricular kuntau. The method used in this research is descriptive qualitative issues related to character values contained in martial arts Kuntau. Data collected by the techniques, observation, interviews, and documentation. These results indicate that the character education through extracurricular activities Kuntau make a positive contribution to the formation and development of student character. Conditions that can develop extracurricular coaching is a mature site planning activities and a regular exercise schedule.Keywords: Character Education, Extracurricular, the Martial Arts Kuntau